anonymous
  • anonymous
(x/2) squared - (y/2) squared=1 find the asymptotes
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Let’s first consider something easier. x^2 – y^2 = 1. This will trace out a hyperbola. The asymptotes are lines that the hyperbola will approach as x goes to infinity. Asymptotes are lines. So we want equations of lines. This suggests we solve for y in terms of x in the hyperbola, and then see what happens to y as x goes to infinity. Our hyperbola is x^2 – y^2 = 1. So y^2 = x^2 – 1. So y = sqrt(x^2 – 1) or y = - sqrt(x^2 – 1). Now, we see that when x goes to infinity, the expression under the square root goes to infinity. So y = sqrt(x^2 – 1) goes off to +infinity and y = - sqrt(x^2 – 1) goes off to – infinity. But what line does it approach? As x becomes large, x^2 – 1 is approximately just x^2. So then y is approximately sqrt(x^2) = x. Therefore, y = x is an asymptote. Similarly, for negative values of y, y = - sqrt(x^2 – 1) means that y is approximately –sqrt(x^2) = -x. So y = x and y = -x are the asymptotes. In general, if your hyperbola is (x/a)^2 – (y/b)^2 = 1, then (y/b)^2 = (x/a)^2 – 1. So y/b = sqrt( (x/a)^2 – 1) or y/b = - sqrt((x/a)^2 – 1). So as x goes to infinity, (x/a)^2 – 1 is approximately just (x/a)^2 since subtracting 1 becomes insignificant. So then y/b is approximately sqrt( (x/a)^2) = x/a. Therefore, y ~ (b/a) * x. Similarly for the negative values of y, y ~ -(b/a) * x. These are your asymptotes for the hyperbola (x/a)^2 – (y/b)^2 = 1. You can also use the same chain of reasoning to find the asymptotes for the hyperbola (y/b)^2 – (x/a)^2 = 1 if you needed to.

Looking for something else?

Not the answer you are looking for? Search for more explanations.